Outcomes of laparoscopic hepatic resection versus percutaneous radiofrequency ablation for hepatocellular carcinoma located at the liver surface: A case–control study with propensity score matching. Issue 6 (8th October 2015) - Ito, Tokuji; Tanaka, Shogo; Iwai, Shuji; Takemura, Shigekazu; Hagihara, Atsushi; Uchida‐Kobayashi, Sawako; Shinkawa, Hiroji; Nishioka, Takayoshi; Kawada, Norifumi; Kubo, Shoji
Abstract: Aim: Percutaneous radiofrequency ablation (P‐RFA) therapy is a widely applied treatment for small hepatocellular carcinoma (HCC); however, local recurrence is a major issue of HCC located at the surface of the liver (surface HCC). The aim of this study was to compare the outcome of laparoscopic hepatic resection (LH) and P‐RFA for surface HCC in case–control patient groups using the propensity score. Methods: Between 2011 and 2013, 40 and 52 patients underwent LH and P‐RFA for surface HCC (≤3 cm, 1–3 nodules). To correct the difference in clinicopathological factors between the two groups, propensity score matching was used at a 1:1 ratio, which resulted in a comparison of 27 patients/group. We compared outcomes between the two groups, with special reference to local recurrence. Results: Clinicopathological variables were well balanced between the two groups. One patient in the LH group was converted to open surgery due to adhesion. The incidence of complications was 0% in the P‐RFA group and 15% (four patients) in the LH group ( P = 0.11); however, none of these four patients in the LH group sustained severe complications. The duration of hospitalization following treatment was longer in the LH group than in the P‐RFA group (12.6 vs 7.6 days, P < 0.01). The incidence of local recurrence was lower in the LH group (0%) than in the P‐RFA group (eight patients [30%], P = 0.004). Conclusion: LH is an effective treatment for surface HCC with regard to control of local recurrence.